2009
DOI: 10.1007/s10522-009-9217-3
|View full text |Cite
|
Sign up to set email alerts
|

The difference in gliosis induced by β-amyloid and Tau treatments in astrocyte cultures derived from senescence accelerated and normal mouse strains

Abstract: Astrocytes react to various neurodegenerative insults rapidly and undergo changes known as gliosis or astrogliosis. In Alzheimer's disease (AD), a wall of reactive astrocytes surrounds senile plaques of β-amyloid (Aβ) and might play an important role in clearing of Aβ. AD is neuropathologically characterized by the co-existence of two pathological structures, senile plaques and neurofibrillary tangles composed of Aβ and Tau protein respectively. However, the molecular mechanisms underlie astrogliosis and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Finally, there is strong evidence for A␤ 42 -induced impairments in mitochondrial transport, dynamics and function that contribute to synaptic degeneration [47,55,56]. suggests that A␤ 42 causes reactive astrogliosis [64] 586 as previously observed in human AD tissues [64] 587 and in cultured animal astrocytes [29,30,66]. It is cultured astrocytes [29,67,71] along with a consequent increase of intracellular Ca 2+ levels leading to exocytotic glutamate release.…”
Section: Primary Cultures Of Cerebral Cortex Neuronsmentioning
confidence: 73%
“…Finally, there is strong evidence for A␤ 42 -induced impairments in mitochondrial transport, dynamics and function that contribute to synaptic degeneration [47,55,56]. suggests that A␤ 42 causes reactive astrogliosis [64] 586 as previously observed in human AD tissues [64] 587 and in cultured animal astrocytes [29,30,66]. It is cultured astrocytes [29,67,71] along with a consequent increase of intracellular Ca 2+ levels leading to exocytotic glutamate release.…”
Section: Primary Cultures Of Cerebral Cortex Neuronsmentioning
confidence: 73%
“…Ageing-prone astrocytes, cultured from senescence-accelerated mice, show a larger degree of gliosis than normal astrocytes, after amyloid-β and tau treatment. Besides gliosis, ageing-prone astroglia show a decrease in the ability to support co-cultured neurons, in comparison to normal astroglial cells [134]. Changes in oxidative stress, tau phosphorylation and glutamate uptake of senescence-accelerated murine astrocytes have been observed consistent with reduced neuroprotective capacity in the ageing brain [70].…”
Section: Glial Changes In Normal Ageingmentioning
confidence: 99%
“…Moreover, it is not known the differential involvement of the main brain cell types, neurons and astrocytes. We and others recently demonstrated that SAMP8 cultured astrocytes exhibited age-related disturbances (García-Matas et al 2008;Lü et al 2008Lü et al , 2009) and reduced neuroprotective capacity (García-Matas et al 2008), when compared with SAMR1 astrocytes. Studies on SAMP8 cultured neurons confirmed some agerelated disturbances, such as reduced mitochondrial functionality and higher vulnerability to oxidative injuries (unpublished results).…”
mentioning
confidence: 85%